SMALL VELOCITIES OF METEOROIDS: INTERRELATION OF SOLAR SYSTEM SMALL BODIES - Andreev, V. V. (Одеські астрономічні публікації, 2017)
Reality and dynamical connection of meteoroids with small velocities are discussed.